2009
DOI: 10.4049/jimmunol.0804159
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma-Immune Cytokines throughout the High-Dose Melphalan-Induced Lymphodepletion in Patients with Multiple Myeloma: A Window for Adoptive Immunotherapy

Abstract: High-dose melphalan (HDM) followed by autologous stem cell transplantation (ASCT) is a standard treatment for patients with multiple myeloma. However, lymphocyte reconstitution is impaired after HDM. Recent work has suggested that the lymphopenia period occurring after various immunosuppressive or chemotherapy treatments may provide an interesting opportunity for adoptive antitumor immunotherapy. The objective of this study was to determine an immunotherapy window after HDM and ASCT, evaluating T cell lymphope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…Supporting this notion, Condomines et al indicated that the early lymphodepletion period after high-dose melphalan and ASCT in myeloma patients represents a window for adoptive immunotherapy (53). Along this line, it has been shown that post-transplant infusion of in vivo vaccine-primed and ex vivo costimulated autologous T cells improved CD4 + and CD8 + T-cell counts and led to the induction of clinically relevant immunity in myeloma patients (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this notion, Condomines et al indicated that the early lymphodepletion period after high-dose melphalan and ASCT in myeloma patients represents a window for adoptive immunotherapy (53). Along this line, it has been shown that post-transplant infusion of in vivo vaccine-primed and ex vivo costimulated autologous T cells improved CD4 + and CD8 + T-cell counts and led to the induction of clinically relevant immunity in myeloma patients (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…30 Similarly, high levels of interleukin-6 could support B-cell recovery. 47 The global expansion of central memory CD8 T cells generically (Figure 3) may explain the previously observed increase in CMV responsiveness seen after autologous T-cell infusion but does not account for the enhanced response to the inactivated influenza vaccine seen exclusively in the primed patients. 29,48 The CD4 T cells were less tolerant of melphalan and, in the absence of a primed post-ASCT infusion, may not have been able to supply sufficient help for B-cell differentiation.…”
Section: Discussionmentioning
confidence: 67%
“…It has been shown that myeloma patients had increased plasma level of immune cytokines, including IL-6, IL-7 and IL-15, following HDM and ASCT, and the presence of IL-7 and IL-15 may contribute to the survival and activation of CD3 + T cells present in the SCT graft. 37 Along this line, the recent report by Dudek-Perić et al 39 showed that limb perfusion of melanoma patients with melphalan led to increased release of IL-1β, IL-6, and IL-8 in the locoregional sera of patients. In a prophylactic vaccination mouse model, the authors showed that melphalan administration in vivo could stimulate a CD8 + T-cell-dependent protective antitumor response.…”
Section: Immunomodulatory Effects Of Melphalanmentioning
confidence: 94%
“…35 Without ASCT, high-dose melphalan causes severe myelosuppression, which affects cells of the immune origin including T and B lymphocytes and NK cells. 36,37 …”
Section: Use Of Melphalan In Cancer Treatmentmentioning
confidence: 99%